ФОРМУВАННЯ ТВОРЧИХ ЗДІБНОСТЕЙ СТУДЕНТІВ ПРИ ВИВЧЕННІ ПЕДАГОГІЧНИХ ДИСЦИПЛІН НА ТЕХНОЛОГІЧНОМУ ФАКУЛЬТЕТІ (Педагогіка вищої та середньої школи, 2008)
In article opportunities of formation of creative abilities of students are shown during teaching pedagogical disciplines on technologists by the check faculty.